PENGGUNAAN MODEL 5E BERBASIS STEAM UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA - Fera Maulidya Sukarno (Jurnal Didaktika Pendidikan Dasar, 2019)
The current research’s objectives are to improve the students’ learning creativity and achievement. This research was designed using Classroom Action Research through the implementation of 5E based on STEAM. The research subjects included 32  of the eighth-graders in  SMP Negeri 1 Subang, West Java Province. The students’ creativity was assessed through air balloon creative product and water rocket using Creative Product Semantic Scale (CPSS). Learning achievements were evaluated on Engage phases in Cycle I and II.  Data analysis results show that the students’ learning creativity was improved and science concepts strengthened through self-construction.  The students’ creative inquiry was also improved. The initial mean achievement was equal to 37.67 in phase Engage of Cycle I was increased to 68.41. In-Engage of Cycle II, the students’ achievement was improved from 35.22 to 79.44.